The Phenomenon Of Dark Humor On Twitter: In-Depth Analysis Through Semantic Study (Journal of Namibian Studies : History Politics Culture, 2023)
This research aims to analyze the types of dark humor found on Twitter and uncover the meanings of dark humor found on Twitter. This study employs a qualitative research design using a semantic approach. The data source for this study is derived from the social media platform Twitter. The data consists of tweets that exhibit dark humor on Twitter. The population for this study is tweets from Twitter users in text format that potentially contain dark humor from the years 2011 to 2023. The sampling technique used in this study is total sampling. Data collection techniques utilized in this study include documentation and note-taking. The results of the study reveal the presence of ten types of dark humor found on Twitter, namely sexual, educational, political, familial, ethnic, medical, thief-related, orphan-related, religious, and mental dark humor. Additionally, the meanings of the dark humor discovered encompass lexical, grammatical, referential, non-referential, denotative, connotative, word, term, conceptual, and associative meanings.